Letter (copy) : Speeches by Senor del Vayo - Citrine, Walter, 1887-1983
012a-0084-001 Secretary's. WMC/KMS/663. 9th June, 1938. Señor Don Pablo de Azcarate, Spanish Embassy, 24, Belgrave Square, S.W.1. Dear Señor de Azcarate, Speeches by Senor del vayo. Many thank for sending me a copy of the speeches made by Senor del Vayo at the League Assembly last month. Yours sincerely, General Secretary. 292/946/12a/84